The impact of fluctuations in boat velocity during the rowing cycle on race time - Hill, H.; Fahrig, S. (Scandinavian Journal of Medicine & Science in Sports, 2009)
In competitive rowing, the fluctuations in boat velocity during the rowing cycle are associated with an increased water resistance of the boat as compared with a boat moving at a constant velocity. We aimed to quantify the influence of the increased water resistance on race time using a mathematical approximation, based on the increase in physiological power being proportional to the 2nd power of boat speed. Biomechanical data (oar force, rowing angle, boat velocity, and boat acceleration) were measured when eight elite coxless pair crews performed a rowing test with a stepwise increasing stroke rate (SR: 20, 24, 28, and 32 min-1) that successively increased the mean boat speed. The results revealed a +4.59 s (SR 24.2) to +5.05 s (SR 31.5) 2000-m race-time difference compared with a boat hypothetically moving without velocity fluctuations. Velocity fluctuations were highly correlated with SR (r=0.93) because the accelerations of the rowers' body mass and the mass of the counteracting boat increase with SR. The possibilities to reduce velocity fluctuations and therefore race time are limited. For elite rowers, race time may be slightly reduced by a moderate reduction in SR that is compensated by an increased force output for each stroke.